Платформа комплексного забезпечення економічної безпеки - Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Trusova, Natalia; Кальченко, Сергій Володимирович; Кальченко, Сергей Владимирович; Kalchenko, Serhii; Терещенко, Максим Анатолійович; Терещенко, Максим Анатолиевич; Tereshchenko, Maksym (My University, 2020)
UK: У статті розглядаються детермінанти забезпечення економічної безпеки мезорівня. Розроблено критерій та блок-схему збалансованості циклів економічної безпеки аграрної галузі з метою досягнення однаковості величини “чистої теперішньої вартості інвестиційних витрат” у галузях аграрного сектору економіки. EN: The search for constructive functions and effective means of preventing the emergence of destabilizing situations in the future requires the definition of the state's own interests in European integration processes, and, in particular, food security, which is especially exacerbated by growing import flows. low-quality food products, their artifi-cial (subsidized) competitiveness in Ukrainian markets. The article deals with theoretical and methodological aspects of the economic security of meso levels. The comprehensive approach to balancing the directions of preserving a favorable institutional environment of economic security of the agrarian industry, with observance of rational parameters of using financial and resource capital, improving the quality of agricultural products in the trend of dynamic growth of investment activity is proved. The proposed approach allows determining the proportional distribution of investments taking into account the speed of change in the profitability of agricultural products in a certain cycle of activity. The interaction of the resource, communication, information, technology and personnel cycles is substantiated to ground the final parameters of changing the complex security of economic. The criterion and block diagram of the balance of the cycles of economic security of the agrarian industry have been developed, with the aim of achieving uniformity of the magnitude of the “net present value of in-vestment costs” by the branch of activity. Each subsystem of economic security clearly demonstrates the real state of each of the so-called areas. The proposed clustering of communication in the form of a territorial-sectoral multi-agro-cluster of the Steppe zone, goes beyond the "simple" horizontal networks of economic security. As part of the multi-agro-cluster it is proposed to create a service center in order to provide services for the use of new agricultural ma-chines in the production process.
Platform of complex ensuring of economic security
Keywords: економічна безпека; аграрні підприємства; аграрна промисловість; мульти-агрокластер; economic security; agrarian enterprises; agrarian industry; multi-agro-cluster